CHANGES OF SCIENTIFIC PARADIGMS AND THEIR IMPACT ON THE PHILOSOPHY OF EDUCATION (EDUCATION IN THE 21ST CENTURY, 2023)
Along with the development of science and technology, unfixed scientific ideas, systems, patterns, principles change and are updated, and sometimes their radical changes lead to scientific revolutions. Such a revolution occurred in the 20th century and completely changed scientific systems, theories and methodological foundations. The classical Newtonian paradigm has been updated, and the quantum-relativistic non-classical paradigm occupies the leading position.It cannot be denied that even technologically advanced civilizations are experiencing a deep moral and ecological crisis today, and science and reason are at a development impasse, and it is simply impossible not to see this.Pedagogy, considered one of the most traditional and inertial sciences, could not remain unaffected by these changes. In this case, the philosophy of education acts as a polyphony of scientific opinions, where they contradict each other, but at the same time complement each other. This is the result of identifying problems in the field of education and ways to solve them. It is the philosophy of education that must create a system of consistent knowledge within the system, where knowledge about the world and man will be harmonious and consistent, without contradictions, and will become the basis for the development of new pedagogical approaches and technologies.The article presents our historical and comparative study of transformations of classical and non-classical scientific paradigms. If in classical paradigms, everything was polarized and the analysis method worked, then we see that in non-classical paradigms everything is the other way around: these poles are brought together and the synthesis method works.Education and pedagogy are not immune from the influence of this process, so our research was conducted in the context of studying the influence of scientific paradigms on education and pedagogical thought.
Keywords: scientific revolution; scientific paradigm; philosophy of education; synergy; training of a teacher; classical and non-classical paradigm